1908
DOI: 10.1002/cber.190804102147
|View full text |Cite
|
Sign up to set email alerts
|

Brasan aus Naphthalin

Abstract: 0.1347 g Sbst.: 025S g,COr, 0.0379 g HsO. -0.1071 g Sbst.: 0 ccni N. C1,HlsO,As. Ber. C 52.17, H 4.66, N 0. Gef. D 51.67, D 4.77, D 0. 402. St. v. Kostanecki und V. Lampe: Brasan auB Naphthalln.Vor fiinf Jahren haben K o s t a n e c k i und L l o y d ' ) ein Umwandlungsprodukt der Muttersubstmz des Brasilins, das sogenannte B r as a n , beschrieben, dem sie auf Grund der Brasilinforrnel von F e u e rs t e i n und K o s t a n e c k i die Formel des B&Phenylen-naphthylen-oxyds (1) zuerteilt haben : 1) Diese Beri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1963
1963
2005
2005

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…It is of interest to note that for quite a number of these compounds, which demonstrated inhibitory activity against SCLC, similar activity was also observed against the SCLC/ CDDP lines. This indicates that many compounds of this series are equally active against both the cisplatin-sensitive and cisplatin-resistant lines, which implies that these banzo [6]naphtho [2,3-d]furan-6,ll-dione derivatives do not exhibit cross-resistance with cisplatin against the smallcell lung cancer lines.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…It is of interest to note that for quite a number of these compounds, which demonstrated inhibitory activity against SCLC, similar activity was also observed against the SCLC/ CDDP lines. This indicates that many compounds of this series are equally active against both the cisplatin-sensitive and cisplatin-resistant lines, which implies that these banzo [6]naphtho [2,3-d]furan-6,ll-dione derivatives do not exhibit cross-resistance with cisplatin against the smallcell lung cancer lines.…”
Section: Resultsmentioning
confidence: 88%
“…The hydroxyl function plays an important role with regard to biological activity. l,3-Dihydroxybenzo [6]naphtho [2,3-d]furan-6,11-dione (5b), which contains two hydroxyl functions, exhibited very good inhibitory activity against SCLC and SCLC/CDDP strains, and demonstrated higher topoisomerase II-mediated DNA cleavage than the anticancer agent teniposide (VM-26). However, the DNA cleavage pattern induced by compounds of this series is different from that induced by VM-26.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Without offering substantial evidence, structure IX was preferred by Liebermann (48) first and by Kostanecky and Lampe (43) later. The accuracy of this choice was confirmed by Chatterjea (24), who prepared the methoxy derivative XI by an unambiguous route and found that the properties of XI are the same as those of the product obtained by alkylation of IX (43).…”
Section: Introductionmentioning
confidence: 99%